Games as educational strategy : A case of tangible interaction for users of alternative and augmentative communication - Sanz, Cecilia Verónica; Guisen, Andrea; Marco, Javier; Baldassarri, Sandra; De Giusti, Armando Eduardo (2013)
This paper presents an application formed by a series of games based on tangible interaction, using an interactive horizontal surface (tabletop), oriented to the educational context. The set of games has been designed for the special education scenario, and in particular, for the development of communicational competencies in users of Augmentative and Alternative Communication (AAC). The tool that groups the set of games is called ACoTI (Augmentative Communication through Tangible Interaction). ACoTI proposes that students, by using conventional toys, interact with the computer to perform various simple and complex association activities. Thus, the focus is to train and develop abstraction processes that favor the communication between the individual and his/her environment. In this case, toys have two essential roles: on the one hand, they act as mediators for individual-computer interaction, and on the other, they help to train students in the abstraction processes required for developing communicational skills. A detailed description of ACoTI is included in this paper, as well as the field work carried out to support its design and implementation, and the assessments carried out to validate both the application and its interaction mode. Initial results and possible future works are also described.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Collaboration Technologies and Systems (2013 may. 20-24 : San Diego), pp. 377 - 381
Keywords: JUEGOS; EDUCACIÓN; INTERACCIÓN HOMBRE-COMPUTADORA